The House that Jill Built : A Lesbian Nation in Formation - Ross, Becki, 1959- (Book collections on Project MUSE., 1995)
In The House That Jill Built, Becki Ross explores the dedicated struggle of a largely white, middle-class group of lesbian feminists to subvert the history of lesbian invisibility and persecution by claiming a collective, empowering, public presence in Toronto during the mid- to late 1970s.